2014
DOI: 10.1074/jbc.m113.511295
|View full text |Cite
|
Sign up to set email alerts
|

Mitochondria Contribute to NADPH Generation in Mouse Rod Photoreceptors

Abstract: Background:The major source of NADPH is considered to be the pentose phosphate pathway. Results: In isolated mouse rod photoreceptors, blocking metabolite entry into mitochondria substantially reduces NADPH generation. Mitochondrial metabolic substrates support NADPH generation. Conclusion: Mitochondria-linked pathways contribute substantially to NADPH generation in mouse rod photoreceptors. Significance: A wide range of photoreceptor cell functions depend on adequate NADPH supply.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
49
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 47 publications
(62 citation statements)
references
References 50 publications
2
49
0
Order By: Relevance
“…Pyruvate dehydrogenase (PDH) is the “gatekeeper” for aerobic glycolysis, and it catalyzes acetyl CoA production from glucose-derived pyruvate for fatty acid synthesis. Notably, acetyl CoA is also the entry point into the TCA cycle, where resulting isocitrate and malate act as precursors for most of the NADPH used in the visual cycle (Adler et al 2014). Consistent with an important role for PDH in cone function, patients with PDH deficiency not only display neurologic abnormalities, they also progress to central vision loss (Brown et al 1994).…”
Section: Resultsmentioning
confidence: 99%
“…Pyruvate dehydrogenase (PDH) is the “gatekeeper” for aerobic glycolysis, and it catalyzes acetyl CoA production from glucose-derived pyruvate for fatty acid synthesis. Notably, acetyl CoA is also the entry point into the TCA cycle, where resulting isocitrate and malate act as precursors for most of the NADPH used in the visual cycle (Adler et al 2014). Consistent with an important role for PDH in cone function, patients with PDH deficiency not only display neurologic abnormalities, they also progress to central vision loss (Brown et al 1994).…”
Section: Resultsmentioning
confidence: 99%
“…The released all- trans retinal is reduced within the rod outer segment to all- trans retinol, which is then transported to the RPE where it is recycled to make 11- cis retinal (Lamb and Pugh, 2004; Saari, 2000; Tang et al, 2013). The reduction of all -trans retinal to retinol is catalyzed by the enzyme retinol dehydrogenase RDH8 (Chen et al, 2012; Maeda et al, 2005) and requires metabolic input in the form of NADPH (Adler et al, 2014; Futterman et al, 1970). 11- Cis and all- trans retinal can both generate lipofuscin precursorsin rod outer segments, as evidenced by measurements of single cell fluorescence (Boyer et al, 2012), as well as of bis -retinoids (Ben-Shabat et al, 2002; Liu et al, 2000; Mata et al, 2000; Quazi and Molday, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…5B) while decreasing flux through citric acid cycle intermediates. Previous studies (47,48) indicated that isocitrate dehydrogenase and malic enzyme can produce NADPH in the photoreceptor cytoplasm. Citrate, made in the matrix, can be transported to the cytoplasm to fuel those enzymes.…”
Section: Evidence For Changes In Anabolic Metabolismmentioning
confidence: 99%